APLIKASI PENGENDALI PERALATAN ELEKTRONIK MENGGUNAKAN RASPBERRY PI PADA PT. SUMBER KAWAN LAMA BERBASIS WEB: APPLICATION CONTROLLER, MICROCONTROLLER, RASPBERRY PI - Pariyadi; Kurniawan, Boy (FORTECH (Journal of Information Technology), 2018)
The development of technology science today is characterized by the emergence of tools that use the application of digital and automatic controllers. Technology becomes a very useful thing for human life, starting from mechanical technology, electricity, and of course telecommunication technology. In this era of globalization, technology is very helpful for human activities to make it easier and more efficient. The use of website technology can now be applied as a control and monitoring system, which is used to control electrical devices, so users simply control from a PC or smartphone that has been connected to Wi-Fi or the Internet. In this case the control using Raspberry Pi which has several advantages such as low power and relatively easy when connected to the web server compared with the microcontroller. By utilizing Raspberry Pi as web server can replace the function of PC in general.